(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
This paper aims at shedding light on issues that translators should consider before deciding on the fees to quote for translating a business film. The paper adopts Mailhac’s (1996, 2000) point of view on the subject. Real examples of these issues are used to help in the calculation and to illustrate the practical audiovisual translation (AVT) modes in translating business films. Fives business fims were selected for tracing the actual existence of Mailhac’s issues and therefore suggesting quotes. The paper’s finding advocates that these issues should be clarified to help translators calculate their fees. The more AVT modes, interlinked issues and discrepancies involved in the translation of a business film, the higher the charge will be. These issues encompass the question of exactly what should be translated as well as other considerations such as synchronisation, the spoken dimension, other content dimensions and on-screen text. Subtitling, dubbing and voice-over are the most widely used modes in rendering business films, although voice-over is the least-used of these.